Pemberdayaan Kesehatan Masyarakat Melalui Edukasi â€œJatekdarsiâ€ bagi Warga Desa Raharja Kota Banjar - Apriani Apriani; Doni Setiawan; Betty Nurhayati; Gina Rifaâ€™atul Mahmudah; Dasilva Siti Datia; Ilham Kerta Wiguna; Selvira Rahma Firdaus (Jurnal Pengabdian UNDIKMA, 2022)
This service activity aims to empower the community in the health sector through Jatekdarsi education so that they can maintain their blood pressure conditions, understand the problem of hypertension, and treatment efforts to prevent complications due to hypertension. The method used was counseling with service partners, namely residents of Raharja village, Kota Banjar. The evaluation instrument for this activity used pre-test and post-test as well as blood pressure examination, which was then analyzed descriptively. The results of this service indicated that the level of knowledge of citizens about hypertension was excellent. It was indicated by the pre-test (75%) and post-test (90%). From the results of the examination of hypertension from 43 respondents who were present, it was known that 33% had high blood pressure (hypertension), 2% had low blood pressure (hypotension), and the rest (65%) had normal blood pressure. These results indicated that the health condition of the residents of Raharja village was quite good. Furthermore, it is hoped that the community can maintain this condition to avoid complications due to hypertension.